Corrosion Inhibition of Cu-Ni (90/10) Alloy in Seawater and Sulphide-Polluted Seawater Environments by 1, 2, 3-Benzotriazole. (12th February 2013) - Boyapati, Venkata Appa Rao; Kanukula, Chaitanya Kumar
Abstract : The inhibiting effect of 1, 2, 3-benzotriazole (BTAH) against the corrosion of Cu-Ni (90/10) alloy in seawater and seawater polluted with inorganic sulphide was studied by electrochemical impedance studies (EISs), potentiodynamic polarization studies, and cyclic voltammetric (CV) and weight-loss studies. Surface examination studies were carried out by X-ray photo electron spectroscopy (XPS) and scanning electron microscopy (SEM)/energy dispersive X-ray analysis (EDX). EIS studies have been carried out in seawater and 10 ppm of inorganic sulphide containing seawater in the absence and presence of BTAH at different concentrations, different immersion periods, and at different temperatures. Appropriate equivalent circuit model was used to calculate the impedance parameters. The potentiodynamic polarization studies inferred that BTAH functions as a mixed inhibitor. The impedance, polarization, and weight-loss studies showed that the inhibition efficiency of BTAH is in the range between 99.97 and 99.30% under different conditions. Cyclic voltammeric studies show the stability of the protective BTAH film even at anodic potentials of +550 mV versus Ag/AgCl. All these studies infer that BTAH functions as an excellent inhibitor for Cu-Ni (90/10) alloy in seawater and sulphide-polluted seawater. XPS and SEM-EDX studies confirm the presence of protective BTAH film on the alloy surface.